PERBANDINGAN PEMERIKSAAN DAN PENJATUHAN SANKSI TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN OLEH ANAK MENURUT SISTEM PERADILAN INDONESIA DAN BELANDA: Comparison Of Examination And Sanctioning Of Murder Committed By Children According To The Indonesian And Netherlands Judicial Systems - Ade Putri Agustini; Abdul Ficar Hadjar (Faculty of Law, Universitas Trisakti, 2024)
Currently, the rate of homicide in Indonesia by children is increasing, which raises concerns in the justice system as children are the next generation of the country's ideals. For this reason, Indonesia stipulates special regulations stipulated in Law No. 11/2012 while the Netherlands in the Wetboek van Strafrecht and Wetboek van Strafvordering. The problem of this artcle is how the similarities and differences regarding the examination and imposition of sanctions for the crime of murder by children according to the Indonesian and Netherlands justice systems. The research method used is descriptive normative legal research method using secondary data obtained from literature study. This research aims to analyze the examination and imposition of sanctions for criminal acts of murder committed by children according to the Indonesian and Netherlands justice systems. The discussion results and the conclusion that the similarities are in the legal system of the country, the elements of the crime of murder, the examination in court, the imposition of sanctions and fostering institutions while the differences are the regulatory provisions, the age limit of the child and the period of time regarding the procedure.